The effect of preemptive local anesthesia on postoperative pain following vaginal hysterectomy: A randomized controlled trial. (December 2021) - Gluck, Ohad; Feldstein, Ohad; Barber, Elad; Tamayev, Liliya; Condrea, Alexander; Grinstein, Ehud; Sagiv, Ron; Wolfson, Inna; Bar, Jacob; Ginath, Shimon
Abstract: Objective: We aimed to study the effect of preemptive local anesthetic without adrenaline on postoperative pain following vaginal hysterectomy and concomitant trans obturator tape (TOT). Study design: This was a double-blinded, randomized, controlled trial. Women who undergone elective vaginal hysterectomy were included. Solutions of either Bupivacaine-Hydrochloride 0.5%, or Sodium-Chloride 0.9% as a placebo, were prepared prior to surgery, according to randomization. The chosen solution was injected before incision, in a circumferential manner, to the cervix. The amount of fluid administered was 10 ml. When colporrhaphy was also performed, an additional 5 ml of solution were injected in the midline of the vaginal wall prior to each incision line. We conformed to the CONSORT recommendations. By utilizing the 10 cm Visual-analogue-scale (VAS) we assessed post-operative pain at rest at 3, 8, and 24 h, and during ambulation at 8 and 24 h. We estimated that the intervention would cause a 25% reduction in the primary outcome. The required total sample size was calculated to be 30 patients women for each group. We used ANOVA for continuous variables and the Chi-square or Fisher exact tests for categorical variables. Results: A total of 30 women were included in each group. The level of postoperative pain, as assessed by VAS, was not significantly different between the groups, in all points of time. In addition, there was no difference between the groups in opioid based analgesics during recovery, nor in postoperative analgesic use. Conclusion: Preemptive local anesthesia was not shown to be efficient in reducing postoperative pain after vaginal hysterectomy and TOT.